Migration Between Mexico and the United States IMISCOE Regional Reader - Escobar Latapí, Agustín; Masferrer, Claudia (IMISCOE Research Series, 2022)
This open access Regional Reader describes how Mexico - United States migration changed substantially during the first decade of the 21st Century. The book provides an in-depth analysis on the changes in the flows into and out of both countries, thus highlighting the issues arising from Mexico - US migration as well as addressing the large numbers of adults and children entering Mexico from the United States. It covers how this tidal change affects the Hispanic population of the U.S. and return migrants' reincorporation in Mexico; their jobs, access to school, health and access to health services, how fear became a dominant aspect of Mexicans' lives in the U.S., and the role played by crime and social policy in Mexico.